Regularly incremented phase encoding – MR fingerprinting (RIPE‐MRF) for enhanced motion artifact suppression in preclinical cartesian MR fingerprinting. Issue 4 (10th August 2017) - Anderson, Christian E.; Wang, Charlie Y.; Gu, Yuning; Darrah, Rebecca; Griswold, Mark A.; Yu, Xin; Flask, Chris A.
Abstract : Purpose: The regularly incremented phase encoding–magnetic resonance fingerprinting (RIPE‐MRF) method is introduced to limit the sensitivity of preclinical MRF assessments to pulsatile and respiratory motion artifacts. Methods: As compared to previously reported standard Cartesian–MRF methods (SC‐MRF), the proposed RIPE‐MRF method uses a modified Cartesian trajectory that varies the acquired phase‐encoding line within each dynamic MRF dataset. Phantoms and mice were scanned without gating or triggering on a 7T preclinical MRI scanner using the RIPE‐MRF and SC‐MRF methods. In vitro phantom longitudinal relaxation time (T1 ) and transverse relaxation time (T2 ) measurements, as well as in vivo liver assessments of artifact‐to‐noise ratio (ANR) and MRF‐based T1 and T2 mean and standard deviation, were compared between the two methods (n = 5). Results: RIPE‐MRF showed significant ANR reductions in regions of pulsatility ( P < 0.005) and respiratory motion ( P < 0.0005). RIPE‐MRF also exhibited improved precision in T1 and T2 measurements in comparison to the SC‐MRF method ( P < 0.05). The RIPE‐MRF and SC‐MRF methods displayed similar mean T1 and T2 estimates (difference in mean values < 10%). Conclusion: These results show that the RIPE‐MRF method can provide effective motion artifact suppression with minimal impact on T1 and T2 accuracy for in vivo small animal MRI studies. Magn Reson Med 79:2176–2182, 2018. © 2017 International Society for Magnetic Resonance in Medicine.